Pengaruh Partisipasi Penganggaran dan Komitmen Organisasi Terhadap Senjangan Anggaran Dengan Ketidakpastian Lingkungan Sebagai Variabel Moderasi - Brata, I Made Putra Wirya; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 24 No 2 (2018)DO - 10.24843/EJA.2018.v24.i02.p27, 2018)
ABSTRACT Agency theory suggests the existence of budget slack practices influenced by the authorization of the principal to the manager to participate in the budget formulation process (budgetary participation) is often misused. The purpose of this study is to obtain empirical evidence regarding the influence of budgetary participation and organizational commitment to budgetary slack with environmental uncertainty as a moderating variable. This research was conducted on all star hotels located in Denpasar city in 2017. The sampling method using purposive sampling. The number of samples of this study are 14 hotels. Data analysis technique used is Moderated Regression Analysis (MRA). Based on the test results, it can be concluded that budgetary participation has a positive effect on budgetary gaps, organizational commitment negatively affect the budget gap, environmental uncertainties strengthen the relationship of budget participation against budget slack is rejected, environmental uncertainty weakens organizational commitment relationship to budget slack is accepted.              Keywords : Budget slack, Budgetary participation, Organizational commitment, Environmental Uncertainty